Generation of monoclonal antibodies specific to ribosomal protein S6 kinase 1 - Savinska, L.O.; Klipa, O.M.; Demchuk, N.O.; Ovcharenko, G.V.; Malanchuk, O.M.; Tykhonkova, I.O.; Palchevskyy, S.S.; Filonenko, V.V. (Вiopolymers and Cell, 2012)
The aim of this study was to produce monoclonal antibodies directed to the N-terminal regulatory region of S6K1, which shows very low homology to S6K2. Methods. Hybridoma technology, ELISA, Western blot, Immunoprecipitation. Results. Three hybridoma clones (A1, A2 and A3) producing mAbs specific to ribosomal protein S6 kinase 1 have been generated. Specificity of mAbs has been confirmed by Western blot and immunoprecipitation technique. Conclusions. The obtained antibodies are suitable for elucidating signal transduction pathways involving S6K1. Keywords: ribosomal protein S6 kinase, mAbs.